Теплоэнергетическая интеграция процесса производства гипофосфита натрия - Товажнянский, Леонид Леонидович; Капустенко, Пётр Алексеевич; Ульев, Леонид Михайлович; Болдырев, Станислав Александрович; Нечипоренко, Дарина Дмитриевна (НТУ "ХПИ", 2009)
The energy consumption in hypophosphite production process was defined after it observation it. The values of hot and cold utilities were defined too. In the paper was shown that heat exchange system have a disadvantages which carry on to big value of energy consumption. With the help of pinch design methods was made the project of heat recuperation system. Use this project can give profit about 1,18 million US dollars in the year. Pay back period of this project is about fourteen months.
Keywords: тепловые системы; теплообменники; теплообмен противоточный; предприятия химические; пинч-проектирование; рекуперация; теплоэнергетика; гипофосфит натрия